Syntax of topic, focus, and contrast : an interface-based approach - Neeleman, Ad; Vermeulen, Reiko (Studies in generative grammar ;, 2012)
"This book addresses how core notions of information structure (topic, focus and contrast) are expressed in syntax. The authorspropose that the syntactic effects of information structure come about as a result of mapping rules flexible enough to allow topics and foci to be expressed in a variety of positions, but strict enough to capture certain cross-linguistic generalisations about their distribution. Syntactic and semantic evidence from a range of languages are discussed"--Provided by publisher.